Kemampuan Komunikasi Matematis Siswa pada Materi Aritmatika Sosial Kelas VII SMP IT Islamilillah Simpang III Pangkalan Susu - Dewi Rulia Sitepu; Ice Wirevenska; Mardiati; Khairina Afni (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the students' mathematical communication skills on Social Arithmetic material for class VII SMP IT Islamilillah Simpang III Pangkalan Susu. This type of research is a descriptive quanittative research. This research was conducted at SMP IT Islamillah Simpang III Pangkalan Susu. The subjects of this study were students of class VII SMP IT Islamilillah Simpang III Pangkalan Susu with a total of 28 students. The object of this research is the mathematical communication ability of the seventh grade students of SMP IT Islamillah Simpang III Pangkalan Susu. Data collection techniques used are tests and interviews. Data analysis was carried out based on the results of tests and interviews referring to the criteria of mathematical communication skills using 6 levels of students' mathematical communication skills. The results showed that the mathematical communication skills of seventh grade students of SMP IT Islamillah on social arithmetic material were at the level of communication skills. This can be seen from the results of the 28 mathematical communication skills test in the low category there are 6 students at level 0 and 8 students at level 1. In the medium category there are 4 students at level 2 and 5 students at level 3. In the high category there are 3 students at level 3. level 4 and 2 students at level 5